Believe #metoo: sexual violence and interpersonal disclosure experiences among women attending a sexual assault service in Australia: a mixed-methods study. Issue 7 (30th July 2019) - Rees, Susan; Simpson, Lisa; McCormack, Clare A; Moussa, Batool; Amanatidis, Sue
Abstract : Objectives: Sexual abuse is a strong predictor of future psychiatric problems. A more nuanced qualitative understanding of mental health outcomes, in the context of interpersonal responses from family members towards survivors after sexual abuse, may help to better inform prevention and interventions. Design: A mixed-methods approach included a qualitative timeline method to map and identify contextual factors and mediating emotional responses associated with mental disorder following sexual abuse. Setting: Participants were adult survivors of sexual abuse, seeking support from the Sexual Assault Counselling Service, Sydney Local Health District, Australia. Participants: Thirty women 18 years and older with current or past mental disorder or symptoms were interviewed between August 2015 and May 2016. Outcome measures: A qualitative timeline interview and the Mini-International Neuropsychiatric Interview (MINI, 5.5.0) were applied. Results: The MINI prevalence of current post-traumatic stress disorder was 96.6% (n=28) and of major depressive disorder was 82.8% (n=24). More than half (53%) reported suicidal ideation at some time in their lives. Women exposed to childhood sexual abuse reported being ignored, not believed, or threatened with retribution on disclosing the abuse to others, usually adult family members, at or close to the time of the violation(s). Participants described experiences of self-blame, betrayal, and psychosocial vulnerability as being the responses that connected negative disclosure experiences with mental disorder. Participant accounts suggest that these reactions created the foundations for both immediate and long-term adverse psychological outcomes. Conclusion: A more in-depth understanding of the type and emotional impact of negative responses to disclosure by parents and other family members, and the barriers to adequate support, validation and trust, may inform strategies to avert much of the longer-term emotional difficulties and risks that survivors encounter following childhood abuse experiences. These issues should receive closer attention in research, policy, and practice.